2007
DOI: 10.1080/10242420701379916
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed synthesis of phenolic lipids from fish liver oil and dihydrocaffeic acid

Abstract: The enzymatic synthesis of phenolic lipids by lipase-catalyzed transesterification of dihydrocaffeic acid (DHCA) with fish liver oil was investigated in a selected organic solvent medium. These synthesized phenolic lipids have potential use as nutraceutical products. Using a molar ratio of 1:8 DHCA to fish liver oil in hexane:2-butanone mixtures of 75:25 and 85:15 (v/v), the lipase-catalyzed reaction resulted in maximum conversion of 55.8 and 65.4%, respectively. The maximum conversion of phenolic monoacylglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…However, the use of phenolic acids as natural antioxidants in foods and nutraceutical supplements has the limitation of low solubility in oil-based media. Nevertheless, lipase-catalyzed reactions of lipids with phenolic acids could produce structured lipids with phenolic moieties, which would have health beneits and improved solubility characteristics [32][33][34][35].…”
Section: Nutritional and Antioxidant Propertiesmentioning
confidence: 99%
“…However, the use of phenolic acids as natural antioxidants in foods and nutraceutical supplements has the limitation of low solubility in oil-based media. Nevertheless, lipase-catalyzed reactions of lipids with phenolic acids could produce structured lipids with phenolic moieties, which would have health beneits and improved solubility characteristics [32][33][34][35].…”
Section: Nutritional and Antioxidant Propertiesmentioning
confidence: 99%
“…The enzymatic processes can be used in the production of fats and oils containing beneficial fatty acids and or/phenolic compounds Karboune et al, 2005;Sabally et al, 2006a,b and2007).…”
Section: Biosynthesis Of Phenolic Lipidsmentioning
confidence: 99%
“…Using lipase as a biocatalyst and substrate models, recent research work in our laboratory Sabally et al, 2005a,b and2006a,b;Safari et al, 2006) confirmed the validity of such an approach. In addition, the synthesis of phenolic lipids, using endogenous oils, such as flax seed oil (Sabally et al, 2006b) and fish liver oil (Sabally et al, 2007), was also reported. The advantages of using enzyme-catalyzed reactions, in comparison to chemical processes, offer an increase in the selectivity of side chains, milder reaction conditions and a more natural approach towards the synthesis of end products (Laane et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, their applications in oil-based food processing and cosmetic industries are limited due to their low solubility in hydrophobic media (Buisman et al, 1998;Figueroa-Espinoza and Villeneuve 2005). To improve the lipophilicity of phenolic acids, an alternative method is incorporation of phenolic acids into triacylglycerols through enzymatic reactions (Compton et al 2000;Sabally et al 2005Sabally et al , 2006Sabally et al , 2007Laszlo and Compton 2006). However, direct transesterification of phenolic acids with triacylglycerols is generally suffered from long reaction time and low efficiency (Figueroa-Espinoza and Villeneuve 2005;Compton et al 2000).…”
Section: Introductionmentioning
confidence: 99%